The Influence of Quality Management Systems on the Success of Information Technology - Deitje S Pongoh; Keira Revalin Kantale; Anastasya Kole; Christian Ivander Wowor; Gio Wonda (Syntax Corporation Indonesia, 2024)
Regarding the influence of quality management systems on the success of information technology (IT), it can be started by explaining the importance of quality in the development and implementation of IT systems. In the context of modern business, information technology plays a very important role in supporting operations, increasing efficiency, and providing competitive advantage. However, to ensure that IT systems truly support these goals, quality in every aspect of IT development and management must be maintained. This study aims to analyze the influence of quality management systems on the success of information technology. In an increasingly complex business environment, the quality of information technology is a determining factor in achieving organizational goals. An effective quality management system is expected to increase efficiency, reduce risk, and ensure that results are in accordance with predetermined specifications.